Two Sources of Justification - Kostyło, Piotr (Paedagogia Christiana, 2015)
The article concerns one of the key doctrines of Christianity – the one of justification which, in the modern times, has become a theological reason for the division of Western Christianity. The author points out that relating the doctrine of justification exclusively to the doctrine of redemption has entailed a number of undesired consequences, e.g. treating life like a sacrifice by many Christians. Showing justification in the light of the doctrine of creation would allow to abandon that pessimistic vision and to turn to treating life like a gift. It would also have a positive impact on religious education.